Development of a model of a biomedical system of vital activity under the influence of electromagnetic radiation - Semenets, V.V.; Stytsenko, T.E.; Grigoriev, A.B. (Radiotekhnika, 2024)
An assessment of the effectiveness of the biomedical protection system has been developed based on the assessment of the dose of the harmful effects of electromagnetic radiation, which allows comparing the existing technical systems according to their level of safety. A functional model of the biomedical vital system with various sources of electromagnetic radiation of the microwave range has been developed based on deterministic criteria, which allow evaluating with a certain probability the performance of the task of functioning of the vital activity system. The statistical criterion is built taking into account the cost of the system, which allows us (when building biological protection systems based on general models) to obtain calculation formulas connecting the newly defined system quality criterion with parameters that can be relatively easily measured and normalized from biological and sanitary considerations, which determines the practical value of the work.